Design and development of curious Jojo© a go-green 3D game on android - Abu Bakar, Juliana Aida; Abdul Mutalib, Ariffin; Permadi, Dendi (Institute of Advanced Engineering and Science (IAES), 2013)
Various campaigns such as ‘Save the Earth’, ‘Earth Hour’, and ‘Reduce, Reuse, Recycle’ are held to create environmental awareness among the general public.The effort is seen endlessly using any means of presentation and communication medium in order to ensure the intended message reach its audience. Meanwhile, the availability of mobile devices and the advent of natural user interfaces have simplified the interaction in games so that it is intuitive for vast audience at different abilities.Hence, this would possibly provide wider audience an engaging experience while playing games and at the same time absorbing the intended message.This article describes the process of designing and developing a go-green tridimensional (3D) game on a mobile platform.It also discusses educational benefits of games and how the concept of environmental awareness is integrated into the game play in order to educate the general public especially the young ones about their social roles.Initial results on performance assessment reveal that the functionality of interactive elements in the game is excellent and young ones did not have difficulties in playing the game.Future work will focus on how 3D mobile games facilitate informal learning process such as inculcating environmental awareness to the general public.